Operation Snow how a Soviet mole in FDR's White House triggered Pearl Harbor - Koster, John (Regnery, 2012)
Recently declassified evidence and never-before-translated documents tell the real story of the day that FDR memorably declared would live in infamy, exploring how Joseph Stalin and the KGB used a vast network of double agents and communist sympathizers--most notably Harry Dexter White--to lead Japan into war against the United States, proposing Soviet involvement behind the bombing of Pearl Harbor
Includes bibliographical references (p. 225-238) and index
Keywords: White, Harry Dexter / 1892-1948; White, Harry Dexter -- 1892-1948; United States / Dept. of the Treasury / Officials and employees / Biography; Sowjetunion -- Narodnyj Komissariat Vnutrennich Del; Geschichte 1900-2000; Geschichte 1941; Moles (Spies); Subversive activities / United States / History / 20th century; Espionage, Soviet / United States / History; Pearl Harbor (Hawaii), Attack on, 1941; Geschichte; Überfall auf Pearl Harbor; USA; Sowjetunion; Japan; Biografie